EFEKTIFITAS VASRIASI PUTARAN DARI PROSES BALANCING TERHADAP PUTARAN KERJA POROS YANG SESUNGGUHNYA - Sulistyono, Djoko; Budiman, Arief (MEKANIKA: Jurnal Teknik Mesin, 2015)
Balancing the goal is to balance the machine or the rotating shaft, which in turn will reduce the vibration.Balancing is done pasa shaft-disk system by responding vibration in five rounds variations balancing: 400 rpm,600rpm, 800rpm, 1000 rpm, 1200 rpm. Retrieval of data by performing the balancing process which furtherbalancing process that responds to vibrations to determine the mass of unbalancenya and a counterweight on theshaft angle disc. Results balancing is then rotated in the other rounds to determine the effectiveness of balancing hasbeen done to change round. The purpose of this test is to get round the balancing effective. The test results showedthat the balancing process is able to reduce the vibration conducted properly, this indicates that balancing is doneon a round shaft below the critical round-the dish is less effective. In addition, the balancing is done on rotationaway from a critical lap is relatively effective. While balancing is done on a round close with a round of critics isrelatively effective. Balancing process that is performed in the round balancing is far from critical rotation hasadvantages over balancing the work done at the round when viewed in terms of security while balancing process isdoneKeywords: balancing, spindle disc, critical round